Implementation Of Finite State Automata In A Laundry Perfume Vending Machine For Clothes And Carpets - Desvia, Yessica Fara; Pratama, Febryawan Yuda; Suhendri, Suhendri (STMIK Subang, 2025)
Perfume is popular among various groups of people, including laundry fragrances. Laundry perfumes come in a variety of scents, such as fruity, floral, a combination of fruit and floral, and woody aromas. These fragrances are typically applied during the final stage of the laundry process. Currently, customers receive their laundry with a randomly selected scent based on the availability at the laundry service, which means they cannot choose the fragrance they prefer. Therefore, a Vending Machine (VM) design is needed to allow customers to select their desired laundry perfume. The VM is designed using the Finite State Automata (FSA) approach, specifically the Non-Deterministic Finite Automata (NFA) type, as it can accommodate multiple conditions for a single option. The development of the NFA method involves stages such as business process analysis, state diagram creation, VM design, and system testing. The results of this study indicate that the implementation of this VM simplifies the process for customers to choose their preferred laundry perfume, ensuring that their laundry has a scent that matches their personal preferences.